Forgotten guidewire presenting as femoral vein extrusion: a rare complication of central venous access - Umit, Tuba Betul; Tugay Saricicek (Journal of the Pakistan Medical Association, 2026)
Central venous catheterisation (CVC) is a commonly performed procedure for critically ill patients in emergency departments (EDs). Here, we present the case of a rare complication of CVC involving a retained guidewire that was forgotten in the patient’s vascular system and spontaneously extruded through the femoral vein 1.5 years later, prompting the patient to seek ED care. Keywords: Central venous catheterisation, Guidewire, Femoral vein, Foreign body.